Database System on Improving Public Services in Supporting the Implementation of Good Governance in the Surabaya City Government - Haganta Ginting, Putri Septriana; Susi Hardjati (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Surabaya City in East Java has been recognized as one of the cities with a responsive and innovative government due to its implementation of good governance, particularly in the development of e-Government. The Surabaya city government utilizes information technology to enhance administrative efficiency, improve transparency and accountability, and encourage public participation in development. This study examines how database systems can improve public services and assist decision-making processes to implement good governance in the Surabaya City Government. To evaluate how database systems contribute to better decision-making and enhanced quality of public services, this research employs a qualitative methodology that includes observation and descriptive analysis. The findings indicate that database systems can enhance service quality, provide clear and accountable governance, and optimize operational efficiency. Furthermore, the integration of